Doing business in emerging markets - Cavusgil, S Tamer, author. 553128; Ghauri, Pervez N, author. 248896; Liu, Leigh Anne, author. (Thousand Oaks : Sage Publishing, 2021)
"Fully updated to include coverage on the recent COVID-19 pandemic as well as other recent macro drivers, this third edition provides a comprehensive and authoritative examination of emerging markets across the globe"--